The The Crisis of Paper Money and the Prospects for Cryptocurrency: An Analysis of the Maqashid al-Shariah Regarding Digital Monetary Instruments - Muh. Baihaqi; M. Andika Yuda Pratama; Dahlia Bonang; Azizi Abu Bakar (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The development of digital monetary systems has posed serious challenges to Islamic financial principles, particularly in the context of the use of fiat money and the emergence of crypto assets. Paper money without real value backing tends to cause economic instability and violations of maqashid al-shariah, particularly in the aspect of hifz al-mal (protection of wealth). On the other hand, cryptocurrencies and Central Bank Digital Currencies (CBDCs) offer potential as alternative instruments, yet they still pose significant Shariah risks. This study aims to evaluate contemporary monetary instruments within the framework of maqashid al-shariah to assess the extent to which they fulfill the principles of justice, public interest, and the protection of the economic value of the ummah. Method: The method employed is qualitative research with a normative-theoretical approach. Data were collected through a literature review of classical maqashid texts (al-Ghazali, al-Shatibi, Ibn Ashur), DSN-MUI fatwas, central bank reports, and digital asset whitepapers. The analytical techniques employed include content analysis of primary and secondary documents, as well as critical discourse analysis to examine dominant narratives within the current financial system. Results: The research findings indicate that the fiat money system possesses structural weaknesses that potentially violate the maqashid. Cryptocurrencies and CBDCs have the potential to fill this gap if designed in accordance with Shariah principles. However, this revised article emphasizes the need for criticism regarding the potential for abuse of state power and mass surveillance in the implementation of CBDCs, which may conflict with other maqashid such as hifz al-nafs (protection of life) and hifz al-hurriyah (protection of freedom). A maqashid-based evaluation has proven effective in assessing the alignment of digital monetary instruments with Islamic values. Conclusion: This study contributes to the development of a maqashid-based evaluative framework for digital financial innovations. Collective ijtihad and synergy between scholars and technologists are required to establish a just and sustainable Islamic monetary system.